Dual activating FGFR1 mutations in pediatric pilomyxoid astrocytoma. - Fomchenko, Elena I; Reeves, Benjamin C; Sullivan, William; Marks, Asher M; Huttner, Anita; Kahle, Kristopher T; Erson-Omay, E Zeynep (Mol Genet Genomic Med, 2021)
BACKGROUND: Pilomyxoid astrocytomas are an aggressive subtype of astrocytoma, not graded by WHO, frequently located in hypothalamic/chiasmatic region, affecting diencephalic structures, and characterized by shorter survival and high recurrence rates. Pilomyxoid astrocytoma management remains controversial, with pathologic tissue diagnosis and relief of mass effect being the main goals of surgery while avoiding treatment-related morbidity, including vision loss, panhypopituitarism, and hypothalamic dysfunction. Chemotherapy (typically vincristine and carboplatin) in all pediatric patients and radiation therapy in pediatric patients over 5 years of age are used for treatment. METHODS: We report clinical presentation, surgical management, and whole exome sequencing results in a pediatric patient with the subtotally resected pilomyxoid astrocytoma. RESULTS: We identified two somatic activating missense mutations affecting FGFR1, including FGFR1 p.K656E and FGFR1 p.V561M. While the former is a known hotspot mutation that is both activating and transforming, the latter has been described as a gatekeeper mutation imparting resistance to FGFR inhibitors. Interestingly, both mutations were present with similar variant allele frequency within the tumor. CONCLUSION: Similar variant allele frequencies of FGFR1 p.K656E and FGFR1 p.V561M mutations in our patient's tumor suggest that these mutations may have occurred at similar time points. Use of FGFR inhibitors in addition to STAT3 or PI3K/mTOR inhibition may prove a useful strategy in targeting our patient's pilomyxoid astrocytoma.

Exome sequencing implicates genetic disruption of prenatal neuro-gliogenesis in sporadic congenital hydrocephalus. - Jin, Sheng Chih; Dong, Weilai; Kundishora, Adam J; Panchagnula, Shreyas; Moreno-De-Luca, Andres; Furey, Charuta G; Allocco, August A; Walker, Rebecca L; Nelson-Williams, Carol; Smith, Hannah; Dunbar, Ashley; Conine, Sierra; et al. (Nat Med, 2020)
Congenital hydrocephalus (CH), characterized by enlarged brain ventricles, is considered a disease of excessive cerebrospinal fluid (CSF) accumulation and thereby treated with neurosurgical CSF diversion with high morbidity and failure rates. The poor neurodevelopmental outcomes and persistence of ventriculomegaly in some post-surgical patients highlight our limited knowledge of disease mechanisms. Through whole-exome sequencing of 381 patients (232 trios) with sporadic, neurosurgically treated CH, we found that damaging de novo mutations account for >17% of cases, with five different genes exhibiting a significant de novo mutation burden. In all, rare, damaging mutations with large effect contributed to ~22% of sporadic CH cases. Multiple CH genes are key regulators of neural stem cell biology and converge in human transcriptional networks and cell types pertinent for fetal neuro-gliogenesis. These data implicate genetic disruption of early brain development, not impaired CSF dynamics, as the primary pathomechanism of a significant number of patients with sporadic CH.
Keywords: Brain; Cerebral Ventricles; Exome; Female; Genetic Predisposition to Disease; Humans; Hydrocephalus; Male; Mutation; Neural Stem Cells; Neurogenesis; Neuroglia; Transcription Factors; Tripartite Motif Proteins; Ubiquitin-Protein Ligases; Whole Exome Sequencing

Exome Sequencing Implicates Impaired GABA Signaling and Neuronal Ion Transport in Trigeminal Neuralgia. - Dong, Weilai; Jin, Sheng Chih; Allocco, August; Zeng, Xue; Sheth, Amar H; Panchagnula, Shreyas; Castonguay, Annie; Lorenzo, Louis-Étienne; Islam, Barira; Brindle, Geneviève; Bachand, Karine; Hu, Jamie; et al. (iScience, 2020)
Trigeminal neuralgia (TN) is a common, debilitating neuropathic face pain syndrome often resistant to therapy. The familial clustering of TN cases suggests that genetic factors play a role in disease pathogenesis. However, no unbiased, large-scale genomic study of TN has been performed to date. Analysis of 290 whole exome-sequenced TN probands, including 20 multiplex kindreds and 70 parent-offspring trios, revealed enrichment of rare, damaging variants in GABA receptor-binding genes in cases. Mice engineered with a TN-associated mutation (p.Cys188Trp) in the GABA receptor Cl channel γ-1 subunit () exhibited trigeminal mechanical allodynia and face pain behavior. Other TN probands harbored rare damaging variants in Na and Ca channels, including a significant variant burden in the α-1H subunit of the voltage-gated Ca channel Ca3.2 (). These results provide exome-level insight into TN and implicate genetically encoded impairment of GABA signaling and neuronal ion transport in TN pathogenesis.

New drugs on the horizon for cerebral edema: what's in the clinical development pipeline? - Robert, Stephanie M; Reeves, Benjamin C; Alper, Seth L; Zhang, Jinwei; Kahle, Kristopher T (Expert Opin Investig Drugs, 2020)
INTRODUCTION: Research has advanced our understanding of the molecular and cellular mechanisms of cerebral edema and has propelled the development of novel antiedema therapeutics. Current evidence supports aberrant neuro-glial ion transport as a central mechanism that underlies pathological fluid accumulation after central nervous system injury. AREAS COVERED: Novel agents in clinical development show potential in altering the natural history and treatment of cerebral edema. Using the PubMed and Google Scholar databases, we review recent advances in our understanding of cerebral edema and describe agents under active investigation, their mechanism, and their application in recent and ongoing clinical trials. EXPERT OPINION: Pharmacotherapies that target molecular mechanisms underlying the compensatory post-injury response of ion channels and transporters that lead to pathological alteration of osmotic gradients are the most promising therapeutic strategies. Repurposing of drugs such as glyburide that inhibit the aberrant upregulation of ion channels such as SUR1-TRPM4, and novel agents, such as ZT-1a, which reestablish physiological regulation of ion channels such as NKCC1/KCC, could be useful adjuvants to prevent and even reverse fluid accumulation in the brain parenchyma.
Keywords: Animals; Brain Edema; Drug Development; Drug Repositioning; Drugs, Investigational; Humans; Molecular Targeted Therapy

EphrinB2-EphB4-RASA1 Signaling in Human Cerebrovascular Development and Disease. - Zeng, Xue; Hunt, Ava; Jin, Sheng Chih; Duran, Daniel; Gaillard, Jonathan; Kahle, Kristopher T (Trends Mol Med, 2019)
Recent whole exome sequencing studies in humans have provided novel insight into the importance of the ephrinB2-EphB4-RASA1 signaling axis in cerebrovascular development, corroborating and extending previous work in model systems. Here, we aim to review the human cerebrovascular phenotypes associated with ephrinB2-EphB4-RASA1 mutations, including those recently discovered in Vein of Galen malformation: the most common and severe brain arteriovenous malformation in neonates. We will also discuss emerging paradigms of the molecular and cellular pathophysiology of disease-causing ephrinB2-EphB4-RASA1 mutations, including the potential role of somatic mosaicism. These observations have potential diagnostic and therapeutic implications for patients with rare congenital cerebrovascular diseases and their families.

De novo mutations in inhibitors of Wnt, BMP, and Ras/ERK signaling pathways in non-syndromic midline craniosynostosis. - Timberlake, Andrew T; Furey, Charuta G; Choi, Jungmin; Nelson-Williams, Carol; Loring, Erin; Galm, Amy; Kahle, Kristopher T; Steinbacher, Derek M; Larysz, Dawid; Persing, John A; Lifton, Richard P (Proc Natl Acad Sci U S A, 2017)
Non-syndromic craniosynostosis (NSC) is a frequent congenital malformation in which one or more cranial sutures fuse prematurely. Mutations causing rare syndromic craniosynostoses in humans and engineered mouse models commonly increase signaling of the Wnt, bone morphogenetic protein (BMP), or Ras/ERK pathways, converging on shared nuclear targets that promote bone formation. In contrast, the genetics of NSC is largely unexplored. More than 95% of NSC is sporadic, suggesting a role for de novo mutations. Exome sequencing of 291 parent-offspring trios with midline NSC revealed 15 probands with heterozygous damaging de novo mutations in 12 negative regulators of Wnt, BMP, and Ras/ERK signaling (10.9-fold enrichment, = 2.4 × 10). had 4 de novo and 14 transmitted mutations; no other gene had more than 1. Four familial NSC kindreds had mutations in genes previously implicated in syndromic disease. Collectively, these mutations contribute to 10% of probands. Mutations are predominantly loss-of-function, implicating haploinsufficiency as a frequent mechanism. A common risk variant near increased the penetrance of mutations and was overtransmitted to patients with de novo mutations in other genes in these pathways, supporting a frequent two-locus pathogenesis. These findings implicate new genes in NSC and demonstrate related pathophysiology of common non-syndromic and rare syndromic craniosynostoses. These findings have implications for diagnosis, risk of recurrence, and risk of adverse neurodevelopmental outcomes. Finally, the use of pathways identified in rare syndromic disease to find genes accounting for non-syndromic cases may prove broadly relevant to understanding other congenital disorders featuring high locus heterogeneity.
Keywords: Adult; Animals; Bone Morphogenetic Proteins; Child; Child, Preschool; Cranial Sutures; Craniosynostoses; Exome; Female; Humans; Male; MAP Kinase Signaling System; Mutation; Osteogenesis; Penetrance; Phenotype; ras Proteins; Sequence Analysis, DNA; Signal Transduction; Smad6 Protein; Whole Exome Sequencing

Digenic mutations of human paralogs in Dent's disease type 2 associated with Chiari I malformation. - Duran, Daniel; Jin, Sheng Chih; DeSpenza, Tyrone; Nelson-Williams, Carol; Cogal, Andrea G; Abrash, Elizabeth W; Harris, Peter C; Lieske, John C; Shimshak, Serena Je; Mane, Shrikant; Bilguvar, Kaya; DiLuna, Michael L; et al. (Hum Genome Var, 2016)
and its paralog encode phosphatidylinositol 5-phosphatases that localize to the primary cilium and have roles in ciliogenesis. Mutations in cause the X-linked Dent disease type 2 (DD2; OMIM# 300555), characterized by low-molecular weight proteinuria, hypercalciuria, and the variable presence of cataracts, glaucoma and intellectual disability without structural brain anomalies. Disease-causing mutations in have not been described in humans. Here, we report the case of an 11-year-old boy with short stature and an above-average IQ; severe proteinuria, hypercalciuria and osteopenia resulting in a vertebral compression fracture; and Chiari I malformation with cervico-thoracic syringohydromyelia requiring suboccipital decompression. Sequencing revealed a novel, DD2-causing 462 bp deletion disrupting exon 3 of and a maternally inherited, extremely rare (ExAC allele frequency 8.4×10) damaging missense mutation in (p.A51V). This mutation substitutes an evolutionarily conserved amino acid in the protein's critical PH domain. analyses of mutation impact predicted by SIFT, PolyPhen2, MetaSVM and CADD algorithms were all highly deleterious. Together, our findings report a novel association of DD2 with Chiari I malformation and syringohydromyelia, and document the effects of digenic mutation of human paralogs. These findings lend genetic support to the hypothesis that impaired ciliogenesis may contribute to the development of Chiari I malformation, and implicates OCRL-dependent PIP metabolism in this mechanism.